Amazing Leonardo da Vinci inventions you can build yourself : learn some hands on history! - Anderson, Maxine, ....- (White River Junction (Vt.) : Nomad, 2006)
From armoured tanks and gliders to 'plastic glass' and drawing machines, this interactive book explores the incredible mind of Leonardo da Vinci through hands-on building projects and activities. Most of Leonardo's inventions were never made in his lifetime and remained sketches in his famous notebooks; kids examine some of these original sketches, and learn about the models Leonardo made of his inventions. From there they delve into detailed step-by-step instructions, diagrams, and templates for each project, which are interspersed with historical facts, biographical anecdotes, and trivia. Most of the building can be done using simple household supplies: construction paper, tape, markers, glue, cardboard tubes, aluminium foil, and cardboard boxes. Background about the Renaissance as a period of remarkable achievement in art and science appears throughout the book.
Keywords: Leonardo da Vinci; Uitvindingen